Development Of Golf Putting Learning Model Based On Synthetic Grass - Aep Rohendi (International Journal of Artificial Intelligence Research, 2022)
The game of golf takes place in various conditions of land contours that vary greatly and must be adapted to different distances, these are all challenges that must be faced by golfers to understand the variables that underlie performance. The main objective of this research is to improve putting skills effectively through the development of a synthetic grass-based golf putting learning model at STKIP Pasundan. The method used to uncover this problem are the Research & development (R & D) development method from Borg and Gall. The sample of this study amounted to 40 students, 20 people as the control group and 20 people as the experimental group. Based on the gain index calculation, it was found that the gain for the experimental class was 0.705. This value is interpreted as being in the high category. Soit can be concluded that the development of an effective synthetic grass-based putting golf learning model